Facebook’s reputation : trials and tribulations - Yue, Tao; Beraite, Raminta (London : Rotterdam School of Management, Erasmus University, 2024)
The case is based on the scandal involving Facebook and Cambridge Analytica, the British data analytics firm that harvested data from 87 million Facebook users without their knowledge or consent. The data was subsequently used to influence voter opinion in favour of Donald Trump’s 2016 presidential campaign, and before the UK’s EU membership referendum (the ‘Brexit’ vote). Although Facebook’s meteoric rise has been peppered with some controversy, the social network is currently embroiled in controversies and debates of a more serious nature and magnitude, from security and privacy of user data to election meddling to role in spreading misinformation, falsehoods, hate speech, and the failing of heeding internal concerns over wrongdoing. In the aftermath of the Cambridge Analytica scandal, Facebook suffered a drop in brand value, reputation, and trust. Paradoxically, user base for a long while continued to grow as did financial performance. Drawing on relevant academic concepts, the case impels students to reflect on the paradoxes confronting Facebook as the ramifications of the scandal unraveled. It allows students to analyze Facebook’s actions and critically think what Facebook should have done to address its reputation crisis, and how it can do to reconcile its commercial and societal interests as well as to rebuild its reputation.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Social responsibility of business -- Case studies; Crisis management -- Case studies